Warehousing Permits Arrangements and Implications for Public Peace and Order in Bandar Lampung City - Harrys Bangkit Tanodo (Fakultas Hukum Universitas Lampung, 2023)
Permits are a legal instrument the government uses to control certain activities. The existence of warehouses in the City of Bandar Lampung that do not yet have permits has resulted in problems with public order and peace. This research will discuss the arrangement of warehousing permits in Bandar Lampung and the implications of issuing warehousing permits for public order and peace. This research uses a normative method by examining Government Regulation Number 29 of 2021 concerning the Implementation of the Trade Sector and an empirical approach using the case study method with a qualitative approach and determining informants based on purposive sampling. The findings obtained in this study were that initially, the warehouse owned by PT YHB (Limited Liability Company Yonatama Harry Bersaudara) did not have a permit. Still, after receiving protests from people who felt disturbed, the warehouse only had a permit. In fact, before the warehouse was used, it should have had a permit. The issuance of the warehouse permit, this justifies the warehouse owner's non-compliance with the licensing regulations. The positive impact on the community is the creation of jobs and an increase in the community's economy and local revenue for the City of Bandar Lampung. In contrast, the negative impact is noise, hampered mobility and damage to roads that disturb the community and changes in regional spatial planning.